Traditional Game “Kaulinan Barudak” to Develop Interpersonal Skills - Sima Mulyadi (SEA-CECCEP, 2021)
The purpose of this study was to determine the differences in the interpersonal skills of students who implemented the traditional game "Kaulinan Barudak" and the control class that used conventional learning models. This research is motivated by interpersonal skills are an important part that must be embedded in every individual. Inculcating intelligent interpersonal behavior must be familiarized with children from an early age, but in reality students' interpersonal skills are still low. The research instruments used in the form of structured observations, field notes, and documentation have been judged by experts in their fields. The results of the research can be obtained that the average post test in the experimental class is higher than the control class. Based on the results of hypothesis testing using the Independent sample t-test formula, it can be concluded that there are differences in the interpersonal skills of students in the experimental class that implements the traditional game "kaulinan barudak" and the control class that uses conventional learning models.